Solid-phase synthesis of biocompatible N-heterocyclic carbene–Pd catalysts using a sub-monomer approach. Issue 22 (15th May 2019) - Cherukaraveedu, Durgadas; Cowling, Paul T.; Birch, Gavin P.; Bradley, Mark; Lilienkampf, Annamaria
Abstract : Biocompatible N-heterocyclic carbene (NHC) based Pd ligands were assembled and loaded with Pd via solid-phase synthesis. Abstract : Taking inspiration from the assembly of so-called peptoids ( N -alkylglycine oligomers) we present a new synthetic methodology whereby N-heterocyclic carbene (NHC) based Pd ligands were assembled using a sub-monomer approach and loaded with Pd via solid-phase synthesis. This allowed the rapid generation a library of NHC–palladium catalysts that were readily functionalised to allow bioconjugation. These catalysts were able to rapidly activate a caged fluorophore and 'switch-on' an anticancer prodrug in 3D cell culture.